HUBUNGAN INTELLECTUAL CAPITAL, KINERJA KEUANGAN DAN NILAI PERUSAHAAN SAAT IPO - Aditya Eka Laksana; Sudarno Sudarno (Diponegoro Journal of Accounting, 2014)
This study aims to examine the relationship of intellectual capital, financial performance and firm’s value at initial public offering (IPO). This study uses Pulic model – Value Added Intellectual Coefficients, this research examines the relationship between the efficiency of value added (VAIC) and firms financial performance (ROA and ROE), then examine relationship the firms financial performance (ROA and ROE) to the firms value at IPO (PBV). Sampling method used in this study is purposive sampling with criteria as follows: (1) The company that do an IPO at Indonesia Stock Exchange (IDX) during 2010-2012 and published financial statements at December 31 completely, (2) The company has audited financial statements from the years 2009-2012, (3) The company has a record of the stock price and number of shares issued at IPO, (4) The company doesn’t experience loss at IPO, (5) The companies have positive book value of equity. Based on these criteria, obtained 66 companies over a three year period of observation. Then, there are 9 samples that included outlier should be excluded from samples of observation. So, a decent amount of the final sample are 57 firms. Data analysis with multilinier regression of ordinary least square. The results of this study indicate that intellectual capital (VAIC) has a significant positive effect on financial performance (ROA and ROE). ROA has a significant negative effect on firm value at IPO (PBV), ROE has a significant positive effect on firm value at IPO (PBV), while intellectual capital (VAIC) does not affect the firm value at IPO (PBV).